The Indole-3-Acetamide-Induced Arabidopsis Transcription Factor MYB74 Decreases Plant Growth and Contributes to the Control of Osmotic Stress Responses - Ortiz-García, Paloma; Pérez-Alonso, Marta-Marina; González Ortega-Villaizán, Adrián; Sánchez-Parra, Beatriz; Ludwig-Müller, Jutta; Wilkinson, Mark D.; Pollmann, Stephan (Frontiers in Plant Science, 2022)
The accumulation of the auxin precursor indole-3-acetamide (IAM) in the ami1 mutant has recently been reported to reduce plant growth and to trigger abiotic stress responses in Arabidopsis thaliana. The observed response includes the induction of abscisic acid (ABA) biosynthesis through the promotion of NCED3 expression. The mechanism by which plant growth is limited, however, remained largely unclear. Here, we investigated the transcriptional responses evoked by the exogenous application of IAM using comprehensive RNA-sequencing (RNA-seq) and reverse genetics approaches. The RNA-seq results highlighted the induction of a small number of genes, including the R2R3 MYB transcription factor genes MYB74 and MYB102. The two MYB factors are known to respond to various stress cues and to ABA. Consistent with a role as negative plant growth regulator, conditional MYB74 overexpressor lines showed a considerable growth reduction. RNA-seq analysis of MYB74 mutants indicated an association of MYB74 with responses to osmotic stress, water deprivation, and seed development, which further linked MYB74 with the observed ami1 osmotic stress and seed phenotype. Collectively, our findings point toward a role for MYB74 in plant growth control and in responses to abiotic stress stimuli.